Superior Vena Cava Obstruction After Pediatric Cardiac Surgery: A Case Series - Synthana, Meta Restu; Wisudarti, Calcarina Fitriani Retno; Kurniawaty, Juni; Deviatika, Fiandila Elvana (Faculty of Medicine, Universitas Padjadjaran, 2026)
Background: Superior vena cava (SVC) obstruction is a rare but potentially life–threatening complication following pediatric cardiac surgery, particularly in patients with congenital heart disease. Mechanical factors related to central venous catheterization and underlying venous anomalies may increase the risk of this condition.Case: We reported a case series of three pediatric patients who developed postoperative SVC obstruction following corrective cardiac surgery and were managed in the intensive care unit (ICU). All patients underwent insertion of a central venous catheter (CVC) via the internal jugular vein for perioperative hemodynamic support. Postoperatively, all patients developed clinical manifestations consistent with SVC obstruction, including facial and upper extremity edema, venous congestion, hemodynamic instability, and reduced urine output. Vascular ultrasonography confirmed partial to severe SVC obstruction in all cases. Two patients had associated anatomical variations, including a persistent left SCV, which may have contributed to altered venous drainage. Management strategies included CVC repositioning or removal, anticoagulation therapy, and surgical release of the obstruction when indicated. These interventions resulted in clinical and hemodynamic improvement in all affected patients.Discussion: This case series highlights the importance of recognizing mechanical and anatomical risk factors for SVC obstruction in pediatric cardiac surgery, including catheter size, tip position, and congenital venous anomalies.Conclusion: careful selection of CVC size, optimal tip placement, and ultrasound guidance for catheter positioning and postoperative assessment may help prevent this serious complication. Early diagnosis and timely intervention are essential to reduce morbidity and improve outcomes in this vulnerable population.